The Application of Restorative Justice at the Jembrana Police Headquarters on the Number of Prisoners at the Negara Class IIB Detention Center - Erikson Sihotang; I Ngurah Agus Dwi Widiatmika Putra; Kadek Dedy Suryana (Al-Makki Publisher, 2026)
The increasing prison population and chronic overcrowding in detention centers have prompted law enforcement to seek alternative approaches beyond conventional punitive measures. Restorative justice offers a solution by focusing on reconciliation, victim-offender mediation, and community-based rehabilitation rather than incarceration. This study examines the implementation of restorative justice at the Jembrana Police Resort and its impact on the number of inmates in the Class IIB State Detention Center. Using a combined normative and empirical legal research method, this study analyzes primary regulations such as the Indonesian National Police Regulation Number 8 of 2021, supported by secondary legal literature. Empirical data were collected through interviews with investigators and detention officials, as well as analysis of case resolution and inmate population records from 2022 to 2024. The results indicate that restorative justice has significantly reduced the number of inmates entering the detention center, with 274 criminal cases resolved through restorative mechanisms during the observed period. This approach not only alleviates overcrowding but also enhances the quality of rehabilitation and reduces recidivism. In conclusion, restorative justice has proven effective as an alternative resolution model in the Jembrana region, supporting decarceration efforts and promoting a more humane justice system. To optimize its impact, recommendations include increasing investigator training, improving inter-institutional coordination, and expanding public awareness of restorative justice mechanisms.